OP0021 Genetic Factors for the Severity of ACPA-Negative Rheumatoid Arthritis in Two Cohorts of Early Disease: A Genome-Wide Study. (23rd January 2014) - De Rooy, D.; Tsonaka, R.; Andersson, M.; Forslind, K.; Zhernakova, A.; de Kovel, C.; Koeleman, B.; van der Heijde, D.; Huizinga, T.; Toes, R.; Houwing-Duistermaat, J.; Svensson, B.; et al.
Abstract : Background: ACPA-negative and ACPA-positive Rheumatoid Arthritis (RA) are increasingly regarded as separate clinical entities. Although ACPA-negative patients have a less severe disease course at group level, considerable inter-individual differences in the amount of joint destruction occur. Objectives: As no studies focusing on genetic risk factors underlying the differences in joint destruction in ACPA-negative patients have been performed thus far, we performed the present study. Methods: A Genome-Wide Association Study was performed using Illumina Human CytoSNP-12v2 in relation to radiographic joint destruction in 276 ACPA-negative early RA-patients included in the Leiden Early Arthritis Clinic (EAC). According to the Bonferroni correction on the number of tested SNPs, the threshold for genome wide significance was p<2x10 -7 . Subsequently, the significant SNPs were evaluated for association with the progression of radiographic joint destruction in 253 ACPA-negative early RA-patients included in the BARFOT-study. As 11 uncorrelated SNPs were tested, the Bonferroni threshold for significance was 0.0045. In all patients, joint destruction was measured by Sharp-van der Heijde Score with good reproducibility. Results: 33 SNPs associated significantly to the severity of joint damage (p<2x10 -7 ) in phase-1. In phase-2, two SNPs showed a trend towards a significant association with joint damage, rs2833522 (p=0.0049) and rs17763915 (p=0.047). A combined analysis of both the Leiden and BARFOT datasets of rs2833522 showed a highly significant association with joint destruction (p=3.57x10 -9 ), the presence of the minor allele associated with more severe damage. Conclusions: Rs2833522 might be associated with the severity of joint damage in ACPA-negative RA. Larger, longitudinal, studies are needed for confirmation. Acknowledgements: This work is supported by the Masterswitch project and BtheCure project. The work of Annette van der Helm-van Mil is supported by the Dutch organization for scientific research (ZonMW). The Dutch Arthritis Foundation (Reumafonds) provided financial support for the genotyping. Disclosure of Interest: None Declared